Let's solve the equation step-by-step.
Starting with: \[ 3(x−5)+2x=0 \]
- Distribute \(3\) into \( (x - 5) \): \[ 3x - 15 + 2x = 0 \]
Now, we can fill in the blanks:
First Blank: -15 (the result after distributing)
Thus, we have: \[ 3x - 15 + 2x = 0 \]
- Combine like terms: \[ (3x + 2x) - 15 = 0 \] \[ 5x - 15 = 0 \]
Now, we can fill in the second blank:
Second Blank: 15 (the number after moving 15 to the other side)
Thus, we have: \[ 5x = 15 \]
- Solve for \(x\) by dividing both sides by \(5\): \[ x = \frac{15}{5} \] \[ x = 3 \]
Now, we can fill in the third blank:
Third Blank: 3 (the value of \(x\))
Putting it all together:
- First Blank: -15
- Second Blank: 15
- Third Blank: 3